Iodine concentration in household salt in South Africa - Jooste Pieter L.; Weight Michael J.; Lombard Carl J. (The World Health Organization, 2001)
OBJECTIVE: To determine the iodine concentration in household salt, the coverage of adequately iodized salt, the use of non-iodized agricultural and producers? salt, and the usefulness of salt as a carrier of iodine, and to relate these observations to socioeconomic status in South Africa. METHOD: The iodometric titration method was used to analyse 2043 household salt samples collected using a national, multistage, stratified, cluster survey. FINDINGS: The national mean and median iodine concentrations of household salt were 27 mg/kg (95% confidence interval (CI): 25-29 mg/kg) and 30 mg/kg (range = 0-155 mg/kg), respectively. There was considerable variation within and between geographical areas. Coverage of adequately iodized household salt, i.e. iodized at >15 mg/kg, was 62.4% of households (95% CI: 58.8-66.0%) two years after the introduction of compulsory iodization at a level of 40-60 mg/kg. A total of 7.3% of households used non-iodized agricultural salt and salt obtained directly from producers. People at the lower end of the socioeconomic spectrum were more likely to suffer the consequences of using under-iodized salt because more of them used agricultural or coarse salt than did people in the higher socioeconomic categories. The iodine concentration in salt was lower in rural areas than in urban and periurban areas. CONCLUSIONS: The consequences of using under-iodized or non-iodized salt were most likely to be experienced in the country?s three northern provinces, among people in the low socioeconomic categories, and in rural households. Since 95.4% of households in South Africa use salt regularly and 2.9% use it occasionally, the national iodization programme has the potential to meet the iodine requirements of the population. However, this can only be achieved if the primary reasons for the inadequate iodization of salt are eliminated and if special attention is given to vulnerable groups.